Changes in enzymatic activity and oxidative stress in honeybees kept in the apiary and laboratory conditions during the course of nosemosis - Magdalena Kunat-Budzyńska; Emilia Łabuć; Aneta A. Ptaszyńska (PLoS ONE, 2025)
The aim of this study was to investigate the changes in the level of oxidative stress and lysozyme-like and phenoloxidase (PO) activity under the influence of nosemosis. Honeybees were kept in natural (apiary) and artificial (laboratory) conditions. In this study, it was shown for the first time that honeybees kept in apiaries have higher levels and activity of the studied parameters than honeybees kept in the laboratory. The greatest difference was noted in the case of PO activity in 28-day-old infected honeybees in May, when the activity was 32.3 times higher in honeybees kept in the apiary than in the laboratory, suggesting that environmental conditions have a significant influence on the immune response of honeybees. Simultaneously, the apiary conditions resulted in higher level of oxidative stress, indicating lower effectiveness of antioxidative mechanisms. Additional nosemosis infection increased the level of oxidative stress as well as lysozyme and PO activities. In July, in 28-day-old infected honeybees kept in laboratory, the highest increase in PO activity (by 10.79 fold) was detected compared to healthy honeybees. This may indicate that infection causes a decrease in the effectiveness of primarily antioxidant mechanisms, whereas immune mechanisms are still activated during infection. Another interesting factor is the age of the honeybees. It was found that in the summer months (June, July) the lysozyme-like and PO activities increased with age, while in the case of oxidative stress the opposite trend was observed, suggesting better effectiveness of both immune and antioxidant mechanisms. Another important element is seasonality, which significantly affected only the lysozyme-like activity. It was found that in July in all the groups studied this activity was higher than in the other months. The results allow us to better understand the mechanisms of honeybee immunity, which are constantly being studied due to the complex social structure created by these insects. Our research emphasizes that honeybee immunity is dynamic and depends on a number of factors, such as environment, age, season or the presence of pathogens.